The Relationship Between Family Support and Quality of Life Improvement of Patients with Diabetes Mellitus in Semarang - Iskim Luthfa; Moch Aspihan; Muhammad Rifqi Lathif (Jurnal Ners, 2019)
Introduction: Diabetes mellitus (DM) is known as the silent killer, where sufferers often do not realize its signs and symptoms and are frequently diagnosed during another health complication. To maintain quality of life, the family is required to provide support, therefore, this study aims to determine the relationship between family and the patient through observational analytic research.Methods: 120 people with DM make up the research sample using an accidental sampling technique, and data analysis was carried out using the Spearman rank test. The results found that 62 respondents (51.7%) agreed to their families providing good support, and 102 (85%) were satisfied with their quality of life.Results: The Spearman test resulted in a P value of 0,000 and R of 0.334. This means the higher the support provided by the family, the greater the increase in quality of life.Conclusion: The suggestions proposed from this study is for health workers to advocate and encourage family in the planning management of DM sufferers in order to improve their quality of life.